Development Financing : Four Essays On External Financing And Domestic Revenue Mobilization In Developing Countries - (:unkn) unknown (My University, 2023)
The achievement of the 17 goals of the 2030 Agenda by developing countries (DCs) is threatened by a considerable financing gap faced by these countries. Thus, domestic resource mobilisation and external financial flows are essential for financing these development goals. Hence, the financing of development in developing countries is at the heart of this thesis. Accordingly, we have divided the thesis into two parts. Chapter 1 analyses the relationship between financial development and non-resource tax revenues in developing countries. Three significant findings emerge from this chapter. First, financial development has a non-linear impact on non-resource tax revenue mobilisation in developing countries in both the long and short run. However, the development of financial institutions affects non-resource tax revenues only in the long run. Furthermore, our results indicate that institutional characteristics are significant for the relationship between tax revenue and financial development. These findings suggest that a wide range of policies focusing on financial development as a channel for tax revenues may only be helpful if there is attention and goodwill for the rule of law and anti-corruption actions. Finally, the government could encourage direct taxation with financial tools. Chapter 2 looks at the impact of South-South cooperation on non-resource tax revenues in Africa, focusing on Chinese aid to Africa. Our estimation results indicate that Chinese aid encourages non-resource tax revenue mobilisation in Africa. In terms of policy implications, these results help to inform policymakers that South-South cooperation is essential for increasing economic infrastructure and thus improving tax compliance to boost non-resource tax revenue mobilisation in Africa. Chapter 3 examines the impact of foreign direct investment (FDI) on tax revenue mobilisation empirically in developing countries. Two significant findings emerge from this chapter. First, foreig
Keywords: African Research